Z razvojem sodobnih tehnologij in naprednih dostavnih sistemov do učinkovitejšega zdravljenja - Kristl, Julijana (Farmacevtski vestnik, 2020)
Development of an optimal drug delivery system is a key factor within development process of a medicine. In concordance with increasing complexity of active pharmaceutical ingredients and medical treatments, advanced drug delivery systems are implemented, contributing to the increased efficiency and prolonged life cycle of medicines. At the Department of Pharmaceutical Technology the contemporary trends in development of innovative delivery systems are successfully followed and expertise based solutions are provided for the challenges arising within industrially established technologies. The present paper represents our most valuable research achievements in the last ten years: development of patient-friendly drug delivery systems, implementation of modern technologies in manufacturing medicines by quality by design, technological approaches for improving solubility and bioavailability of active pharmaceutical ingredients, mukoaddevelopment of stable biopharmaceutics and nanocarriers, all for the purpose of more effective therapy.
Keywords: bolnikom prijazni dostavni sistemi; Dostavni sistemi; Farmacevtska tehnologija; Farmacevtske oblike; lipidni sistemi; nanozdravila; stabilni biofarmacevtiki; večenotne farmacevtske oblike; zdravila z vgrajeno kakovostjo